2015
DOI: 10.1007/s00247-015-3317-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI as a reliable and accurate method for assessment of posterior hip dislocation in children and adolescents without the risk of radiation exposure

Abstract: Intraoperative pathological findings at the time of open surgical treatment were universally recognized on MRI but not on CT scans. MRI should be considered for evaluation of the hip following closed reduction for the treatment of a posterior dislocation in children and adolescents as it reliably allows assessment of intra-articular pathology without the risk of radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…In a series of 40 patients under 16 years old, Mayer et al reported that all surgically confirmed soft-tissue injuries were preoperatively identified on MRI, which also offered the advantage of absence of radiation in that age group. 13 CT scan may especially lead to underestimation of an osteochondral lesion at the posterior wall. 13 14 In the present case, a tear at the posterior labral complex, which lead to complete enfoldment of the posterior labrum, and an additional osteochondral fragment resulted in the nonconcentric joint after closed reduction of the hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 40 patients under 16 years old, Mayer et al reported that all surgically confirmed soft-tissue injuries were preoperatively identified on MRI, which also offered the advantage of absence of radiation in that age group. 13 CT scan may especially lead to underestimation of an osteochondral lesion at the posterior wall. 13 14 In the present case, a tear at the posterior labral complex, which lead to complete enfoldment of the posterior labrum, and an additional osteochondral fragment resulted in the nonconcentric joint after closed reduction of the hip.…”
Section: Discussionmentioning
confidence: 99%
“… 13 CT scan may especially lead to underestimation of an osteochondral lesion at the posterior wall. 13 14 In the present case, a tear at the posterior labral complex, which lead to complete enfoldment of the posterior labrum, and an additional osteochondral fragment resulted in the nonconcentric joint after closed reduction of the hip. Similarly, treatment of an incarcerated acetabular labrum following reduction of a traumatic hip dislocation has been effectively reported with either refixation or excision of an osseo-labral fragment via hip arthroscopy in adults.…”
Section: Discussionmentioning
confidence: 99%
“…kombinierte Frakturen tendenziell nicht mit der MRT abgeklärt worden waren. Gemäß Literatur kam die MRT bisher bei Azetabulumfrakturen nur in gesonderten Fällen wie ausgedehnten Weichteilschäden (Morell-Lavallée-Läsion) oder pädiatrischen/adoleszenten Verletzungen zum Einsatz [26,27]. Meist ist die Azetabulumfraktur komplex und macht eine operative Rekonstruktion der Gelenkfläche erforderlich.…”
Section: Frakturlokalisationunclassified
“…2,27 Magnetic resonance imaging (MRI) has been used to supplement CT scans; however, the cost effectiveness of MRI and its ability to identify small bony fragments are debated. 2,28 Postoperative Prosthetic Dislocation Assessment Dislocations after total hip replacement are usually a result of low-energy trauma; however, high-energy dislocations occur and require a more detailed secondary survey. Prosthetic dislocations are a time-sensitive medical emergency.…”
Section: Native Dislocation Assessmentmentioning
confidence: 99%